PENGARUH AKTIVITAS FOREIGN BUY DAN FOREIGN SELL TERHADAP HARGA SAHAM EMITEN SEKTOR PERBANKAN MILIK NEGARA PADA INDEKS LQ45 DI BURSA EFEK INDONESIA - Mahfuddin, Rohmat; Munaf, Tommy (EKONOMIKA, 2023)
This study aims to determine the effect of foreign buy and foreign sell activity on government bank companies stock price in LQ45 of Indonesia Stock Exchange. This research focuses on daily period from 1 January 2022 to 31 January 2022 with 4 companies as the population. Determination of the sample was done by saturation sampling method and 4 companies were chosen. This type of research is quantitative research. The type of data used is secondary data that collected from stock securities firm named ‘Ajaib’ using documentation and literature methods. The data is presented with panel data which will be processed using multiple linier regression analysis method through Eviews 12. The results of this study indicate that foreign buy activities has a positive significant effect towards stock price and foreign sell activities has negative but not significant effects on stock prices. Based on the results of the F test, the conclusion is foreign buy and foreign sell activities has a significant effect on stock prices